Climate protection as an ethical challenge - Karaczun, Zbigniew M. (Studia Ecologiae et Bioethicae, 2017)
Mitigation of global climate change is one of the most important challenges facing humanity in the 21st century. It will require significant changes in the economy, consumption, the style of life. However, climate protection is also an ethical problem. It is a problem of responsibility for the climate – the common good of all creatures. This article discusses selected ethical issues that are related to the implementation of climate policy. It was indicated that the acceptance of research results indicating human responsibility for climate change is a prerequisite for active climate action. It has also been found that the common but differentiated responsibility of individual countries is primarily due to their historical greenhouse gas emissions. It also results from the fact that most of the significant negative impacts of climate change will occur in the poorest countries, whose share of greenhouse gas emissions is very small. The rejection of human responsibility for climate change and the responsibility of rich societies for already occurring changes and their effects in developing countries means that climate mitigation actions are not being sufficiently addressed. Behind Pope Francis repeated that without changing ethical attitudes towards the natural environment and accepting responsibility for the whole world around us, effective climate protection would not be possible.